2022
DOI: 10.18240/ijo.2022.06.18
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and awareness of glaucoma in Mexican patients with and without glaucoma diagnosis in an Ophthalmology Referral Center

Abstract: AIM: To assess and compare knowledge and awareness of glaucoma in subjects with and without glaucoma diagnosis attending an Ophthalmology Referral Center. METHODS: This cross-sectional study was conducted at Asociación Para Evitar la Ceguera in Mexico City, using a questionnaire formulated by a group of experts following the Delphi panel rules, and pre-tested in a pilot study. The questionnaire was applied and compared between: glaucoma patients, relatives of glaucoma patients and patients without glaucoma. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Our findings show that gender has no relationship with knowledge or awareness, similar to previous studies [1,4,5,9,18,20,22]. There is no relationship between age and awareness of Glaucoma, Like a previous study [9,15,18,20,26]. And in contrast to previous studies that showed a relationship between older age and awareness [2,3,5,14], another study showed that the knowledge of the youngest was greater, but not by a significant [1].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our findings show that gender has no relationship with knowledge or awareness, similar to previous studies [1,4,5,9,18,20,22]. There is no relationship between age and awareness of Glaucoma, Like a previous study [9,15,18,20,26]. And in contrast to previous studies that showed a relationship between older age and awareness [2,3,5,14], another study showed that the knowledge of the youngest was greater, but not by a significant [1].…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, a sufficient sample should be gained in the case of accurate results. In previous studies, social relations were mentioned as the most important source of knowledge [ 1 , 4 , 9 , 15 , 18 , 26 , 27 ], and in other studies, the Internet was the most important [ 5 ], health workers [ 20 ]. In our study, the most important are social relations.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 221 (37.8%) participants had heard about glaucoma, compared with 73.9% in a survey in Mexico [ 16 ], 16.9% in a study at two family health centers in Istanbul [ 17 ], and 26.1% in a study in North India [ 18 ]. These differences may be attributed to regional differences in awareness campaigns, healthcare facilities, and public education programs, resulting in variations in glaucoma knowledge among study participants.…”
Section: Discussionmentioning
confidence: 96%
“…Low medication adherence can reflect the uncertainty of patients about the methods of application and the difficulty in administering the drops [26] , and new strategies must be developed such as creating new containers that are easier to handle for the elderly. Educational strategies must be carried out to get information to the population, brochures should be available on various shelves of health care units so that patients can be informed, also knowing that patients prefer an oral explanation, brochures, videos and exhibits could be held and/or illustrative educational videos could be shown in the waiting rooms to inform patients [27] .…”
Section: Discussionmentioning
confidence: 99%